Different clinical presentations of metachronous pulmonary metastases after resection of pancreatic ductal adenocarcinoma: Retrospective study and review of the literature - Lovecek, Martin (World J Gastroenterol, 2017)
AIM: To analyze pancreatic cancer patients who developed metachronous pulmonary metastases (MPM) as a first site of recurrence after the curative-intent surgery. METHODS: One-hundred-fifty-nine consecutive pancreatic ductal adenocarcinoma (PDAC) patients who underwent radical pancreatic surgery between 2006 and 2013 were included in this retrospective analysis. The clinical data including age, sex, grade, primary tumor location, pTNM stage, lymph node infiltration, microangioinvasion, perineural invasion, lymphovascular invasion, the therapy administered, and follow-up were all obtained from medical records. Further analysis covered only patients with metachronous metastases. Clinical and histopathological data (age, sex, grade, primary tumor location, pTNM stage, lymph node infiltration, microangioinvasion, perineural invasion, lymphovascular invasion, the therapy administered and follow-up) of patients with metachronous non-pulmonary metastases and patients with metachronous pulmonary metastases were statistically assessed. Disease-free survival (DFS) from pancreas resection until metastases onset and overall survival (OS) were calculated. Wilcoxon test, χ(2) test and survival functions computed by the Kaplan-Meier method were used. Statistical significance was evaluated by the log-rank test using SPSS. A P-value of less than 0.05 was considered statistically significant. RESULTS: Metachronous pulmonary metastases were observed in 20 (16.9%) and were operable in 3 (2.5%) of PDAC patients after a prior curative-intent surgery. Patients with isolated pulmonary metastases (oligometastases and multiple metastases) had estimated prior DFS and OS of 35.4 and 81.4 mo, respectively, and those with metachronous pulmonary metastases accompanied by other metastases had prior DFS and OS of 17.3 and 23.4 mo, respectively. Patients with non-pulmonary metastases had prior DFS and OS of 9.4 and 15.8 mo, respectively. Different clinical scenarios according to the presentation of MPM were observed and patients could be divided to three subgroups with different prognosis which could be used for the selection of treatment strategy: isolated pulmonary oligometastases, isolated multiple pulmonary metastases and pulmonary metastases accompanied by other metastases. CONCLUSION: Surgery should be considered for all patients with isolated pulmonary oligometastases, but the risk of intervention has to be individually weighted for each patient.